Social Media Overload: Unraveling the Impact on Academic Performance among University Students in Western Odisha: Media Sosial yang Berlebihan: Mengungkap Dampaknya terhadap Kinerja Akademik di antara Mahasiswa Universitas di Odisha Barat - Deepak Kumar Behera (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
Social networking sites (SNS) have become an integral aspect of university students' daily lives globally, prompting extensive debates about their impact on academic performance. To further explore this topic, we conducted a statistical analysis of SNS's influence on academic performance among university students in Western Odisha, India. This study aims to investigate the extent of SNS usage, examine the relationship between SNS usage and academic performance, and explore the factors influencing SNS usage in this population. Adopting a quantitative research approach, we employed a cross-sectional survey design to collect data from 300 university students in Western Odisha. The collected data underwent rigorous analysis, including descriptive statistics, correlation analysis, and multiple regression analysis. The findings revealed that a majority of university students in Western Odisha extensively use SNS for socialization, entertainment, and academic-related activities. However, a significant negative correlation was observed between SNS usage and academic performance, indicating that increased SNS engagement was associated with lower academic achievements. Additionally, multiple regression analysis demonstrated that SNS usage, time spent on SNS, and internet addiction were significant predictors of academic performance. The implications of this study underscore the importance of raising awareness among university students in Western Odisha about the detrimental impact of excessive SNS usage on academic performance. Moreover, interventions promoting healthy SNS usage practices are crucial to mitigate these negative effects. Our findings contribute to the existing literature on the influence of SNS on academic performance and offer valuable insights for policymakers, educators, and parents in addressing this pertinent issue.